Nitrogênio mineral em um latossolo em função de sistemas de manejo do solo e de culturas de cobertura de inverno - Marafão, Daiana (2016)
The increasing advancement of agriculture makes providing adequate conditions for the growth and development of plants is the primary purpose of soil management systems. Much of the success of PD is attributed to cultural remains left by cover crops that do not require high nitrogen inputs and can thus be used to reduce nitrogen input in the agro- ecosystem. The nitrogen is one of the elements applied in agriculture, it is absorbed in higher quantities and limiting the yield of grain crops such as corn. Thus, there has been the influence of the no-till and conventional tillage combined with different crops of winter cover and bare soil when in succession to corn, on mineral nitrogen content. The experimental work was made at the experimental station of the Agronomic Institute of Paraná - Iapar. The implemented design was blocks at random split plot with three replications in factorial 6 x 2 x 3 x 5. The main plots were as treatment, beyond the bare soil, 5 winter species (ryegrass, vetch, vetch + oat, oat and radish), while in the subplots were used two tillage systems (No-till and conventional tillage). Three collections made were (before management, the urea before and after the urea), these being held in 5 depths (0-5, 5-10, 10-20, 20-40 and 40-60 cm). So a layer 0-5 cm and a que presents increased amount to NH4 + ion. The use of associated PD system in the presence of winter cover crops decreased as NO3 - losses in soil profile.